Solid Pseudopapillary Neoplasm of the Pancreas: Case Series of a Rare Tumor - Sapkota, Simit; Pandit, Subhas; Shakya, Vikal C; Neupane, Sameer (Journal of Institute of Medicine Nepal, 2023)
Solid pseudopapillary neoplasm (SPN) is an infrequent type of pancreatic tumor that primarily occurs in young females. This case series reports three cases of SPN at Civil Service Hospital from 2012-2022. Patients' median age was 18 years; one of the patients presented with painless lump; and the other two had abdominal pain and dullness at presentation. Pre-operative investigations like CT/MRI and fine-needle aspiration cytology confirmed SPN in all cases. All patients received resection treatment, and no adjuvant therapy was administered. During follow-ups lasting 4-7 years, none of the patients experienced recurrence, indicating that surgical resection is the mainstay of treatment with an excellent prognosis.